Automating Microsoft Azure infrastructure services - Washam, Michael (O'Reilly Media, 2015)
Get valuable tips and techniques for automating your cloud deployments with Azure PowerShell cmdlets, and learn how to provision Azure services on the fly. In this hands-on guide, Microsoft cloud technology expert Michael Washam shows you how to automate various management tasks and deploy solutions that are both complex and at scale.